Short-Term Versus Long-Term Portfolio Management Strategies and the Selection of Securities - Haryanto, Joko Tri (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study examines the effectiveness of short-term versus long-term portfolio management strategies and the selection of securities. It aims to provide insights into how different strategies impact investment performance, considering risk tolerance and financial goals. Research Design and Methodology: The study synthesizes findings from academic journals and empirical research using a qualitative literature review approach. The methodology involves thematic analysis to identify key themes, patterns, and insights related to portfolio management strategies and security selection. Findings and Discussion: The research highlights that short-term strategies like momentum trading can capitalize on transient market inefficiencies but entail higher transaction costs and volatility. Conversely, long-term strategies, such as value investing, focus on fundamental analysis and offer more stable returns over time. The integration of ESG criteria into security selection is shown to enhance portfolio performance and align investments with sustainability objectives. Behavioral biases and technological advancements also significantly influence portfolio management decisions. Implications: The study underscores the importance of balancing short-term and long-term strategies based on investor risk tolerance and financial goals. Financial practitioners can leverage these insights to design diversified portfolios and offer tailored advice. Future research should explore the dynamic interplay between these strategies and the impact of technological and regulatory changes on portfolio management. Integrating ESG considerations is crucial for sustainable investing and aligning with evolving market dynamics.